INTEGRASI DEEP LEARNING BERBASIS PENDIDIKAN ISLAM UNTUK MENINGKATKAN LITERASI TEKNOLOGI DAN TANTANGAN MASA DEPAN - Nakhma ussolikhah; Dindin Syarief Nurwahyudin; Ficky Adi Kurniawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The era of technological transformation faces global challenges in the form of digital inequality, a sustainability crisis, and increasing socio-economic disparities. This condition does not only occur at the global level, especially in rural areas. In the era of the Fourth Industrial Revolution, rural communities are faced with limited access to quality education and low use of digital technology for socio-economic progress. This shows that there is a gap in the development of a model that integrates deep learning based on Islamic values ​​with direct village economic empowerment programs. This model internalizes Islamic values ​​such as good morals, trust, ihsan, and maslahah. Its uniqueness lies in the link between learning and practice of village economic empowerment, including the development of micro, small and medium enterprises; marketing digitalization; application of agricultural technology; as well as strengthening community-based technological literacy. Community service will begin in July - August 2025, digging in-depth field data. Data collection was carried out through field observations, in-depth interviews with teachers, village heads, MSME actors, and community leaders, as well as Focus Group Discussions to identify challenges, potential, and strategies for implementing the model. The location of the service is in Karang Suwung Village, Cirebon. Service activities find four main achievements. First, in terms of social indicators, there has been a change in behavior from individual interaction to a collaborative learning culture through mosque-based study groups, digital farming communities and MSME forums. Practically, it is a sustainable model to strengthen technological literacy while encouraging the economic independence of village communities. The novelty of this research lies in the synergistic combination of Islamic education based on in-depth learning and village economic empowerment programs, which have not been widely discussed before. This model has the potential to be replicated in various rural areas in Indonesia on a sustainable basis.